High performance parallelism pearls : multicore and many-core programming approaches. Volume two - Reinders, James; Jeffers, Jim.; ScienceDirect eBooks (Waltham, MA : Morgan Kaufmann an imprint of Elsevier, 2015)
High Performance Parallelism Pearls Volume 2 offers another set of examples that demonstrate how to leverage parallelism. Similar to Volume 1, the techniques included here explain how to use processors and coprocessors with the same programming - illustrating the most effective ways to combine Xeon Phi coprocessors with Xeon and other multicore processors. The book includes examples of successful programming efforts, drawn from across industries and domains such as biomed, genetics, finance, manufacturing, imaging, and more. Each chapter in this edited work includes detailed explanations of t.
For more informationChapter 6: Amber PME Molecular Dynamics Optimization; Theory of MD; Acceleration of neighbor list building using the coprocessor; Acceleration of direct space sum using the coprocessor; Additional optimizations in coprocessor code; Removing locks whenever possible; Exclusion list optimization; Reduce data transfer and computation in offload code; Modification of load balance algorithm; PME direct space sum and neighbor list work; PME reciprocal space sum work; Bonded force work; Compiler optimization flags; Results; Conclusions; For more information.
Print version record.
Chapter 7: Low-Latency Solutions for Financial Services Applications.
Safari Books Online
Elsevier
Keywords: Parallel programming (Computer science) -- Data processing; Coprocessors; Computer programming; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Electronic books